Synthesis of morphology controlled PtAu@Ag nanorings through concentric and eccentric growth pathways. Issue 81 (27th September 2021) - Lee, Junghwa; Lee, Sungwoo; Kim, Jeongwon; Yoo, Sungjae; Lee, Soohyun; Son, Jiwoong; Hilal, Hajir; Go, Sungeun; Lee, Jaewon; Nam, Jwa-Min; Park, Sungho
Abstract : We report the synthetic pathway (concentric and eccentric growth) for Ag on PtAu nanorings to synthesize morphology-controlled Ag nanorings. Abstract : We report the synthetic methodology for silver nanorings with controlled nanoscale morphology. The morphology of Ag nanorings was kinetically controlled by electrochemical potential tuning of Ag deposition using halide counter-ions, which resulted in concentric PtAu@Ag nanorings ( i.e., Ag homogeneously wrapped around the Pt nanorings) and eccentric PtAu@Ag nanorings ( i.e., Ag selectively deposited at the inner boundary of the Pt nanorings). The resulting high quality of each Ag nanoring allowed us to systematically investigate their corresponding localized surface plasmon resonance (LSPR) profiles as a function of their geometrical parameters. Additionally, we evaluated the application of the samples as surface-enhanced Raman spectroscopy (SERS) substrates composed of 2D monolayers of varied compositions of Ag and Au nanorings, which showed a different extent of enhancement depending on the adsorption characteristics of the analytes.